Raspberry Pi essentials : get up and running with the Raspberry Pi to develop captivating projects - Creasey, Jack (Community experience distilled., 2015)
Programmers new to the Raspberry Pi and novice programmers with little to no experience with micro board computing will find the book useful. A basic knowledge of programming languages in general will prove useful for a better understanding of the topics.